Predictive marker for exposure-driven haematological toxicity of tegafur-uracil and proposed modified-dosage regimen by pharmacometric approach in rats. (3rd July 2022) - Kobuchi, Shinji; Matsui, Megumi; Ito, Yukako
Abstract: Myelosuppression is a dose-limiting toxicity of uracil-tegafur (UFT), which contains uracil and the 5‑fluorouracil prodrug tegafur, and inhibits the continuation of chemotherapy, causing treatment failure. A proper dosing strategy to avoid severe myelosuppression-induced discontinuation of chemotherapy is required. Plasma drug concentrations were determined in rats after single oral UFT administration of 15, 30, or 60 mg/kg. Blood cell counts were also measured after oral UFT administration for 5 days. Pharmacokinetic-toxicodynamic (PK-TD) modelling and simulation were performed to describe the time-course alterations in the blood cell counts. Severe neutropenia was observed in rats treated with 60 mg/kg UFT on day 7. A significant decrease in neutrophil counts from baseline levels prior to UFT administration was observed on day 3, whereas leukocyte and lymphocyte counts decreased on day 7. The semi-physiological PK-TD model successfully captured alterations in neutrophil counts after UFT administration, whereas the model could not well describe the platelet, leukocyte, and lymphocyte counts, possibly due to the absence of severe thrombocytopenia, leukocytopenia, and lymphocytopenia, respectively. Neutrophils are sensitive markers for estimating the grade of haematological toxicity of UFT, and a PK-TD model might be an attractive tool for quantitatively evaluating the onset and degree of myelosuppression.